A biomechanical analysis of 1-on-1 offense's feint motion with a dribble in basketball - Hashizume, J.; Ae, M.; Otsu, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purposes of this study were to classify 1 an-I feint motion with a dribble in basketball by the cluster analysis and to investigate the biomechanical characteristics of the classified one. The subjects were ten male varsity basketball players. The 1-on-1 feint motion with a dribble in basketball were classified into 4 types; Anterior-Posterior (AP) type, Shaking- Left- Right (S-LR) type, Shaking-Anterior-Posterior (S-AP) type, Left-Right (LR) type by the Ward method of the hierarchical duster analysis with Euclidean distance measure based on the relative COM velocity and relative foot position. The AP and LR types that an offensive player took large step at switching without shaking the COM were likely to be easy to defend, but shaking the COM was an effective technique to get a head of a defensive player.